Iron Intermetallic Compounds (IMCs) Formation Mechanism in the Molten Aluminium Zinc (Al-Zn) Coating Alloy - Abdul Khaliq; Vishnu Kasva; Abdulaziz S. Alghamdi; Mohamed Ramadan; Tayyab Subhani; Waseem Haider; K. S. Abdel Halim (Tehnički Vjesnik, 2024)
To prevent corrosion of steel products, the steel industry often relies on Al-Zn based alloy coatings, applied through hot-dip coating technology. Despite this, a long-standing problem in the galvanizing industry involves the formation of Fe-based intermetallic compounds (IMCs) in the Al-Zn coating bath, caused by iron dissolution from steel products. Such IMCs are the primary source of dross formation in the Al-Zn bath, which inevitably leads to metal spot defects in the coated steel products and bottom dross build-up in the Al-Zn bath. The present research aims to investigate the mechanism of Fe transformation into IMCs. To achieve this, Fe saturated and unsaturated Al-Zn alloys were doped with low carbon steel at a temperature of 600 °C. The samples were collected at regular intervals and quenched in water. The optical microscopy (OM) and scanning electron microscopy (SEM) with energy dispersive x-ray spectroscopy (EDS) were used to study the transformation of steel strips into Fe-IMCs particles in molten Al-Zn alloys. The study findings suggest that the Fe transformation into Fe-IMCs is a complex process, where the steel strip surface is initially oxidized, and Al5Fe2 and Al3Fe are formed, which finally transform into Al8Fe2Si(Zn) (τ5c) IMCs particles. These results can assist galvanizers in understanding formation of Fe-IMCs and bottom dross build up in the costing pots.